2015
DOI: 10.1371/journal.pone.0125842
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Basic Reproductive Number (R0) for African Swine Fever Virus (ASFV) Transmission between Pig Herds in Uganda

Abstract: African swine fever (ASF) is a highly contagious, lethal and economically devastating haemorrhagic disease of domestic pigs. Insights into the dynamics and scale of virus transmission can be obtained from estimates of the basic reproduction number (R 0). We estimate R 0 for ASF virus in small holder, free-range pig production system in Gulu, Uganda. The estimation was based on data collected from outbreaks that affected 43 villages (out of the 289 villages with an overall pig population of 26,570) between Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…Computation of R0 was derived from the growth rate of cases [17], an approach already applied to ASF for both wild boar (e.g., in Russia [18]) and domestic pigs (e.g., in Uganda [19] and in Ukraine [20]). The assumption of this approach is that at the beginning of the epidemic, the cumulative distribution of the cases grows at an exponential rate, during which each case produces R0 new cases during the infectious period.…”
Section: R0 Estimation Methodsmentioning
confidence: 99%
“…Computation of R0 was derived from the growth rate of cases [17], an approach already applied to ASF for both wild boar (e.g., in Russia [18]) and domestic pigs (e.g., in Uganda [19] and in Ukraine [20]). The assumption of this approach is that at the beginning of the epidemic, the cumulative distribution of the cases grows at an exponential rate, during which each case produces R0 new cases during the infectious period.…”
Section: R0 Estimation Methodsmentioning
confidence: 99%
“…Even though, in many cases, a holding was quarantined before the ASF confirmation, it has been reported that the transmission of the virus could have happened even after quarantine being imposed (Anonymous, ). To reflect the uncertainty on this parameter, two other values of a farm's infectious period were taken from the literature: 15 days (Gulenkin et al., ) and 30 days (Barongo et al., ). The entire period from 10th February to 2nd July 1977 was divided into equal periods of duration D¯bf; the number of newly infected holdings N t was calculated for each period, which resulted in the construction of the epidemic curve. An exponential model was fitted to the observed incidence during the initial stage of the epidemic, that is from the onset of the epidemic to its peak (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…We accepted these values as boundary scenarios, while 7 days was taken as a median scenario being a mean typical infectious period of ASF in pigs ( D wf ) used in the literature (Table ).
Summary of modelling studies estimating the transmission parameters of ASFV in domestic pigs (see also Guinat et al., ) Study Genotype Virus isolate Duration of infectious period, days Between‐farm R 0 Within‐farm R 0 Belyanin et al., IIVarious6.8 (5.0–8.6)De Carvalho Ferreira et al., ; IMalta'786.8 ± 1.818.0 (6.90–46.9)Netherlands'864.6 ± 1.44.92 (1.45–16.6)Pietschmann et al., IIArmenia'082–96.1 (0.6–14.5)5.0 (1.4–10.7)Guinat et al., IIGeorgia 2007/13–142.8 (1.3–4.8) within pen1.4 (0.6–2.4) between penGulenkin et al., IIStavropol 01/085 within farm2–38–1115 between farmBarongo et al., IXUganda30 between farm3.24 (3.21–3.27)1.63 (1.6–1.72)1.90 (1.87–1.94)1.581.77 (1.74–1.81)Current studyIO–777 within farm1.65 (1.42–1.88)7.46 (5.68–9.21)19 between farm
Three epidemic waves were observed in the course of epidemics in th...…”
Section: Methodsmentioning
confidence: 99%
“…Kenya, Malawi, Mozambique, Tanzania, Uganda and Zambia have experienced multiple to frequent outbreaks (Table ). The endemic occurrence of ASF in domestic pigs has subsequently been documented in several Eastern African countries: Kenya (Gallardo, Ademun, et al, ; Gallardo, Okoth, et al, ; Lichoti et al, ; Okoth et al, ), Madagascar (Randrianantoandro, Kono, & Kubota, ; Ravaomanana et al, , ; Roger, Ratovonjato, Vola, & Uilenberg, ), Malawi (Haresnape, Lungu, & Mamu, , ); Mozambique (Penrith et al, , ; Quembo et al, ), Tanzania (Misinzo et al, ; Wambura, Masambu, & Msami, ), Uganda (Atuhaire, Afayoa, Ochwo, Mwesigwa, Okuni, et al, ; Barongo et al, ; Gallardo, Ademun, et al, ; Muhangi et al, ; Muwonge et al., ) and the Eastern Province of Zambia (Samui, Mwanaumo, & Chizyuka, ; Samui et al, ; Simulundu et al, , ; Wilkinson et al, ).…”
Section: History Current Status Transmission Cycles Recent Outbreamentioning
confidence: 99%